The effect of RCAN1 on the biological behaviors of small cell lung cancer - Ningqiang Ma; Weiwei Shen; Hailin Pang; Ning Zhang; Hong Shi; Jianlin Wang; Helong Zhang (Tumor Biology)
Bone is the third most common site of cancer metastasis. In total, 30%–40% of lung cancer cases can develop skeletal metastasis for which no effective therapy in clinic is available. RCAN1 (regulator of calcineurin 1) is an important regulator in angiogenesis which is vital to tumor growth. In this study, we investigated the changes of biological behaviors in SBC-5 and SBC-3 cells after the RCAN1 expression level was changed. Briefly, overexpression of RCAN1 significantly attenuated their malignancy, including decreased ability of proliferation, colony formation, migration, invasion, and bone adherence. Furthermore, the cell cycle progression was impeded. Although the opposite changes were observed in SBC-3 cells after the RCAN1 expression was suppressed by RNA interference, the apoptosis rate was not affected by the expression level of RCAN1 in these cells. So, our research revealed that RCAN1 was involved in the development of small cell lung cancer, and it might be a cancer-inhibiting gene for the formation of bone metastases in small cell lung cancer.